Neighborhood Typology and Cardiometabolic Pregnancy Outcomes in the Maternal Adiposity Metabolism and Stress Study. Issue 1 (4th December 2018) - Headen, Irene; Laraia, Barbara; Coleman‐Phox, Kimberly; Vieten, Cassandra; Adler, Nancy; Epel, Elissa
Abstract : Objective : This study aimed to assess associations between neighborhood typologies classified across multiple neighborhood domains and cardiometabolic pregnancy outcomes and determine variation in effectiveness of a mindfulness‐based stress‐reduction intervention on outcomes across neighborhood types. Methods : Neighborhoods of participants in the Maternal Adiposity Metabolism and Stress (MAMAS) intervention ( n  = 208) were classified across dimensions of socioeconomic, food, safety, and service/resource environments using latent class analysis. The study estimated associations between neighborhood type and three cardiometabolic pregnancy outcomes—glucose tolerance (GT) during pregnancy, excessive gestational weight gain, and 6‐month postpartum weight retention (PPWR)—using marginal regression models. Interaction between neighborhood type and intervention was assessed. Results : Five neighborhood types differing across socioeconomic, food, and resource environments were identified. Compared with poor, well‐resourced neighborhoods, middle‐income neighborhoods with low resources had higher risk of impaired GT (relative risk [RR]: 4.1; 95% confidence Interval [CI]: 1.1, 15.5), and wealthy, well‐resourced neighborhoods had higher PPWR (beta: 3.9 kg; 95% CI: 0.3, 7.5). Intervention effectiveness varied across neighborhood type with wealthy, well‐resourced and poor, moderately resourced neighborhoods showing improvements in GT scores. PPWR was higher in intervention compared with control groups within wealthy, well‐resourced neighborhoods. Conclusions : Consideration of multidimensional neighborhood typologies revealed important nuances in intervention effectiveness on cardiometabolic pregnancy outcomes.